Exorcising translation towards an intercivilizational turn - Robinson, Douglas 1954- (New York Bloomsbury Academic, 2017)
A major new work in translation studies and comparative literature, looking at the tensions and relations between western and eastern culture and literature, by a pioneering scholar in the field"
Includes bibliographical references and index.
Keywords: Translating and interpreting -- Cross-cultural studies; Literature -- Translations -- History and criticism; Literature and transnationalism; East and West